Abu Dhabi's Vision 2030 an ongoing journey of economic development - Low, Linda. (World Scientific Pub. Co., 2012)
This book aims to tell the Abu Dhabi story in economic development, from its past dominance in oil to its economic vision for the future. More than being an exemplar of industrial restructuring and diversification from a resource-based to a 21st century knowledge-based economy and society, Abu Dhabi emphasises its cultural legacy and tradition as an environmental advocate for green and sustainable pathways. It has as many challenges as creative responses to show that its success is not by wealth alone. This case study unveils Abu Dhabi in particular and the rest of Arabic and GCC economic development in general. They have all attracted foreign investment and global business, typically as hydrocarbon-rich resource economies. Beyond that, the geoeconomics and geopolitics of the Middle East and North Africa, with or without the Arab Spring in 2011 is in and of itself, a rich region for multidisciplinary studies and research, not just for economics and business. With Qatar, Abu Dhabi boasts of one of the highest per capita income in the world; therein lies a reason to enquire about its success and pivotal role in the GCC and global contexts.